(untitled) (Tempo e Argumento, 2012)
This article aims to propose some reflections about the issues discussed by popular music on the theme of American Conquest in the teaching of American history. These compositions thematize both the genocide and silencing of indigenous people and their resistance. In the case of musical productions spread mainly in the years 1970-1990, these compositions take the perspective of a "history of the vanquished" on the contrary to the prospect of an epic history of the conquests as told by more traditional approaches.